The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/dcr.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mesenteric Lengthening Techniques in IPAA: An Anatomic and Angiographic Study on Fresh Cadavers

Abstract: Stepladder incisions through superior mesenteric pedicle trace are usually sufficient for mesenteric lengthening. In addition, division of the superior mesenteric pedicle with either a preserving marginal artery or without preserving ileocolic and marginal arteries leads to additional mesenteric lengthening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Several methods for enabling the ileal pouch to reach the anus have been reported, including sufficient mobilization of the small intestine, division of the mesenteric vessels supplying blood to the pouch, and performing transmesenteric incisions [ 6 - 16 ]. Cadaveric studies demonstrated the efficacy and safety of division of the ileocolic artery (ICA) or branches of the superior mesenteric artery (SMA) [ 6 , 7 , 10 , 12 , 16 ], and surgical results of each technique in single-center studies have been reported [ 5 , 8 , 9 , 11 , 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for enabling the ileal pouch to reach the anus have been reported, including sufficient mobilization of the small intestine, division of the mesenteric vessels supplying blood to the pouch, and performing transmesenteric incisions [ 6 - 16 ]. Cadaveric studies demonstrated the efficacy and safety of division of the ileocolic artery (ICA) or branches of the superior mesenteric artery (SMA) [ 6 , 7 , 10 , 12 , 16 ], and surgical results of each technique in single-center studies have been reported [ 5 , 8 , 9 , 11 , 13 , 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 This results in mesenteric lengthening of approximately 3 to 6 cm in cadaveric studies. 24,25 In a small prospective review, this did not result in increased postoperative morbidity. 26 However, it is important to note that SMA ligation results in an increased distance between the distal ileum to the point of greatest reach which may necessitate resection of a short segment of small bowel to ensure proper pouch size.…”
Section: Sma Ligationmentioning
confidence: 90%
“…Relaxing incisions, or "step ladder incisions," can be made anterior and posterior in the mesentery or windows within the mesentery (Fig. 9.4) [18]. Finally, transillumination of the mesentery can identify arcades providing points of safe mesenteric vessel transection, again enabling further lengthening of the mesentery for additional reach of the ileal reservoir for anal anastomosis [19].…”
Section: Small Bowel Mobilizationmentioning
confidence: 99%